From Fear to Fluency: Self-Recorded Video Use to Improve EFL Speaking Proficiency - Neli Fitri Rohdina; Joko Priyana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Speaking is a fundamental skill for students learning English as a Foreign Language (EFL). However, many learners struggle with speaking, which could be due to anxiety, lack of confidence, or limited media for practice. This study investigated the effectiveness of self-recorded video activities in improving students' speaking proficiency. It employed a Classroom Action Research (CAR) approach. Data were collected from pre-tests, post-tests, questionnaires, observations, and interviews among tenth-grade students at SMAN 1 Kedondong. The findings revealed that self-recorded videos significantly enhance students' pronunciation, fluency, coherence, and speaking confidence. Statistical analysis of the test scores indicated measurable improvement with increased motivation and engagement. Students reported a positive learning experience even though they were faced with initial challenges, such as discomfort with self-recording and technical difficulties. Therefore, English teachers are encouraged to adopt the self-recorded video technique as an alternative approach to teaching speaking skills.